Badminton technique, tactics, training - Edwards, John (Crowood sports guides, 1997)
This guide provides practical advice for learning basic skills, advancing techniques and tactics, and reviewing the fundaments of badminton. It features kit checks, rules checks and key points, and the skills and techniques for every level are discussed, with advice on correct equipment.